2013
DOI: 10.1111/2049-632x.12029
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of fibronectin-binding protein to pathogenesis ofStreptococcus equissp. zooepidemicus

Abstract: Streptococcus equi ssp. zooepidemicus (S. zooepidemicus) is responsible for a wide variety of infections in many species. Fibronectin-binding protein is a bacterial cell surface protein, which specifically binds fibronectin (FN). Considering the specific role of FN-binding protein in host-pathogen interactions, we investigated the function of a novel FN-binding domain in the FN-binding protein (FNZ) of S. zooepidemicus. Five recombinant FNZ gene fragments [N1 (amino acids, 38-197), N2 (amino acids, 38-603), N3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Interestingly, it has been reported that in Staphylococcus epidermidis , EmbP is expressed only in the presence of serum . Bacteria possess different mechanisms to recognize fibronectin and other proteins that are present in host‐cell membranes . However, it is still unclear if these molecules are signals that trigger biofilm formation or if they only play a physical role in cell‐surface interactions.…”
Section: Heterologous (Signaling) Molecules That Alter Biofilm Formatmentioning
confidence: 99%
“…Interestingly, it has been reported that in Staphylococcus epidermidis , EmbP is expressed only in the presence of serum . Bacteria possess different mechanisms to recognize fibronectin and other proteins that are present in host‐cell membranes . However, it is still unclear if these molecules are signals that trigger biofilm formation or if they only play a physical role in cell‐surface interactions.…”
Section: Heterologous (Signaling) Molecules That Alter Biofilm Formatmentioning
confidence: 99%
“…zooepidemicus has also been found to occur in a wide range of other animals and in humans . In China, it is the main pathogen causing disease in swine . Putative virulence factors of S. equi ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Two weeks after the second booster dose, the mice in groups 1–3 were inoculated intraperitoneally with 0.2 mL of bacterial suspensions (1.25 × 10 6 cfu/mL, approximately 5 × LD 50 ) obtained from an 18-h culture in THB to evaluate the protection against an S. equi spp. zooepidemicus challenge [ 14 , 15 ]. Another eight mice in Group 4 were injected with 0.2 mL of sterile PBS.…”
Section: Methodsmentioning
confidence: 99%
“…A S. equi spp. zooepidemicus colony was inoculated into 5 mL of THB and was cultivated with shaking at 37 °C for 12 h (late exponential/stationary growth phase) [ 15 ]. The culture was diluted 1:100 with fresh THB broth supplemented with 1% fibrinogen and with either 1% pooled mouse anti-rGroEL serum or 1% pooled non-immunized mouse sera from day 35.…”
Section: Methodsmentioning
confidence: 99%